¿Negociación salarial secuencial o simultánea? - Barcena-Ruiz, Juan Carlos; Campo, María Luz (Estudios de Economía, 2016)
This paper analyzes the timing of wage bargaining in an unionized market whenworkers can be organized in firm level unions or in an industry-level union. Inequilibrium, the result obtained depends on who decide the timing of thenegotiations: the workers or the firm’s owners.